دور القاضي الجزائري في مجال التحكيم الدولي - تخنوني, أسماء (Revue jurisprudence, 2018)
إن نظام "التحكيم" في العالم كبديل لحل النزاعات يرتبط أساسا بتطور الاجتهاد القضائي "القضاء الفرنسي أنموذجا"، سواء من خلال تصور حدود مجال إعمال قواعده، أو عبر قبول نفاذ أحكامها، وإلزام الأطراف الذين ارتضوا وسيلة التحكيم لحل منازعاتهم على تنفيذ مقرراته، والكل لا يمكن أن يتحقق إلا من خلال رقابة قضائية متزنة وحكيمة، تدرك أهمية نظام "التحكيم "كخيار لفض المنازعات، وكمؤشر على التنمية الاجتماعية، الثقافية، الاقتصادية، السياسية، والأمنية وطنيا ودوليا، كما يعتبر اتفاق التحكيم الحجر الأساس أو مركز الثقل في بناء التحكيم كنظام لحل نزاعات التجارة الدولية. الكلمات المفتاحية: اتفاق التحكيم، شرط التحكيم، مشارطة التحكيم.   The "arbitration" system in the world as an alternative to conflict resolution is primarily related to the development of jurisprudence, "the French judiciary, as a model", either by concealing the limits of the scope of its rules or by accepting the entry into force of its rules; and obliging parties that have accepted the arbitration method to resolve their disputes, It can only be achieved through judicious and judicious judicial oversight that recognizes the importance of the system of arbitration as an option for resolving disputes and as an indicator of social, cultural, economic, political and security development nationally and internationally. The arbitration agreement is also considered the cornerstone or center of gravity in the construction of arbitration Trade disputes International. Keywords : arbitration agreement_ arbitration clause_ arbitration clause.